Evaluation of four sorghum hybrids through the development of gluten-free beer - Veith, Kirstin Nicole (Kansas State University, 2009)
There is a limited market of gluten-free beer for the 1% of the US population that is diagnosed with an autoimmune response to gluten protein known as celiac disease. Sorghum can be malted and used in the brewing process to replace malted barley, a grain toxic to celiac patients. The objective of the study was to develop an optimum brewing procedure for a gluten-free ale-style beer. Four different sorghum hybrids (82G63, 83G66, RN315, and X303) were malted and used in brewing gluten-free ale and evaluated for physical and chemical property differences. The four sorghum hybrids were characterized first as grain and then as malt using proximate analysis, single kernel characterization system (SKCS), amylose, α-amylase, and β-amylase contents. Isolated starch from unmalted and malted samples was evaluated with differential scanning calorimetry (DSC). Malt was evaluated throughout the malting process and percent nitrogen, percent moisture, 72 hr germinative energy, steep out moisture, germination-end, and malting loss were measured. Malted sorghum hybrid samples were milled into grist, and employed in a double mash, double decoction brewing process. Following the brewing process the wort was evaluated for specific gravity, Brix, pH, color and free α-amino nitrogen (FAN). Wort was also analyzed using HPLC for ethanol and glucose content. The fermented beer was analyzed for specific gravity, Brix, pH, alcohol by volume, and color. HPLC was also used to measure ethanol and glucose content. Results of analysis found that a significant difference (p=0.05) was found for the DSC data onset temperature, which ranged from 61.75 to 65.51, illustrating the difference in starch gelatinization temperature compared to other cereals. A significant difference was found in α-amylase content (p=0.05) which ranged from 0.16 to 058 in unmalted sorghum and 71.63 to 96.44 in malted sorghum. In addition, α-amylase and β-amylase contents increased during malting. HPLC analysis of wort indicated a significant difference was found in percent maltose which ranged from 1.27 to 2.81. FAN content of wort was also significantly different and ranged from 65.15 to 151.37. HPLC of beer showed a significant difference in percent ethanol and percent glucose. Percent ethanol in the final beer ranged from 3.28 to 4.17 and percent glucose range from 0.16 to 0.31. Process development evaluation indicated a gluten-free ale style beer could be successfully produced with 100% sorghum malt.
Keywords: Sorghum; Gluten free; Beer; Gluten free beer; Malt; Sorghum malt; Agriculture, Food Science and Technology (0359)